Research impact of general and funded papers: a citation analysis of two ACM International Conference Proceeding Series. Issue 4 (8th August 2016) - Shen, Cheng-Che; Hu, Ya-Han; Lin, Wei-Chao; Tsai, Chih-Fong; Ke, Shih-Wen George
Abstract : Purpose: This paper focuses on examining the research impact of papers written with and without funding. Specifically, the citation analysis method is used to compare the general and funded papers published in two leading international conferences, which are ACM SIGIR and ACM SIGKDD. Design/methodology/approach: We investigate the number of general and funded papers to see whether the number of funded papers is larger than the number of general papers. In addition, the total citations and the number of highly cited papers with and without funding are also compared. Findings: The analysis results of ACM SIGIR papers show that in most cases the number of funded papers is larger than the number of general papers. Moreover, the total captions, the average number of citations per paper, and the number of highly cited papers all reveal the superiority of funded papers over general papers. However, the findings are somewhat different for the ACM SIGKDD papers. This may be because ACM SIGIR began much earlier than ACM SIGKDD, which relates to the maturity of the research problems addressed in these two conferences. Originality/value: The value of this paper is the first attempt at examining the research impact of general and funded research papers by the citation analysis method. The research impact of other research areas can be further investigated by other analysis methods.